Connecting Sarcomere Protein Mutations to Pathogenesis in Cardiomyopathies: The Development of “Disease in a Dish” Models - Zaunbrecher, Rebecca; Regnier, Michael (Frontiers in Physiology, 2016)
Recent technological and protocol developments have greatly increased the ability to utilize stem cells transformed into cardiomyocytes as models to study human heart muscle development and how this is affected by disease associated mutations in a variety of sarcomere proteins. In this perspective we provide an overview of these emerging technologies and how they are being used to create better models of ‘disease in a dish’ for both research and screening assays. We also consider the value of these assays as models to explore the seminal processes in initiation of the disease development and the possibility of early interventions.